2023
DOI: 10.3390/jimaging9010014
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Devices’ Influence on User Neck Pain during the COVID-19 Pandemic: Collaborating Vertebral-GLCM Extracted Features with a Decision Tree

Abstract: The prevalence of neck pain, a chronic musculoskeletal disease, has significantly increased due to the uncontrollable use of social media (SM) devices. The use of SM devices by younger generations increased enormously during the COVID-19 pandemic, being—in some cases—the only possibility for maintaining interpersonal, social, and friendship relationships. This study aimed to predict the occurrence of neck pain and its correlation with the intensive use of SM devices. It is based on nine quantitative parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Kross et al (2013), Balakrishnan and Shamim (2013), Beardsmore (2015) and Karim et al (2023) reported the effect of facbook, WhatsApp and Instagram usage on the psychological stress. Similarly, Gupta et al (2022), Al-Naami et al (2023) and Pirnes et al (2023) suggested that increased time spent on social media platforms was associated with neck pain. Also, frequency of checking notifications on phone has been reported to be a factor associated with psychological stress and neck pain in few studies.…”
Section: Development Of the Path Analysis Modelmentioning
confidence: 94%
“…Kross et al (2013), Balakrishnan and Shamim (2013), Beardsmore (2015) and Karim et al (2023) reported the effect of facbook, WhatsApp and Instagram usage on the psychological stress. Similarly, Gupta et al (2022), Al-Naami et al (2023) and Pirnes et al (2023) suggested that increased time spent on social media platforms was associated with neck pain. Also, frequency of checking notifications on phone has been reported to be a factor associated with psychological stress and neck pain in few studies.…”
Section: Development Of the Path Analysis Modelmentioning
confidence: 94%
“…LBP helps characterise binary texture by calculating the local texture and disparity. The method assigns a size of 5 × 5 to each target pixel, and each time, the method selects a pixel and analyses it according to 24 adjacent pixels [40]. The method compares the grey levels of the central (g c ) and adjacent (g p ) pixels according to Equation (7).…”
Section: Splitting Of the Eye Disease Datasetmentioning
confidence: 99%
“…A classifier is a classification algorithm that accumulates and processes hierarchical characteristics extracted from image data. Thus, input identifiers are assigned to images, and then automatic training is performed, as described in [ 44 , 59 ].…”
Section: Deep Learning (Dl) Techniques Used To Identify Face Masksmentioning
confidence: 99%